2001
DOI: 10.1021/jo015790p
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Pauson−Khand Reactions Using Camphor-Derived Chelating Thiols as Chiral Controllers

Abstract: A convenient procedure for the preparation of enantiopure 10-(R-thio)-2-exo-bornanethiols from (1S)-camphor-10-thiol has been developed. The ethynyl derivatives of these thiols gave excellent diastereoselectivities (up to 98:2) in Pauson-Khand reactions with norbornene and norbornadiene through the intermediacy of a chelated dicobalt pentacarbonyl complex. Thermal reaction conditions starting from the preformed chelated complex gave better results than N-oxide-promoted runs with in situ generation of the chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Marchueta et al have developed a convenient procedure for the preparation of enantiopure 10-( R -thio)-2- exo -bornanethiols 153 from (1 S )-camphor-10-thiol 152 (Scheme ). Their ethynyl derivatives 154 led to excellent diastereoselectivities (up to 98:2) in Pauson–Khand reactions with norbornene and norbornadiene through the intermediacy of a chelated dicobalt pentacarbonyl complexes 155 . It was found that thermal reaction conditions starting from the preformed chelated complexes were more efficient than N -oxide-promoted runs with in situ generation of the chelated intermediates.…”
Section: Introduction Of Chirality During the Generation Of The Cyclo...mentioning
confidence: 99%
“…Marchueta et al have developed a convenient procedure for the preparation of enantiopure 10-( R -thio)-2- exo -bornanethiols 153 from (1 S )-camphor-10-thiol 152 (Scheme ). Their ethynyl derivatives 154 led to excellent diastereoselectivities (up to 98:2) in Pauson–Khand reactions with norbornene and norbornadiene through the intermediacy of a chelated dicobalt pentacarbonyl complexes 155 . It was found that thermal reaction conditions starting from the preformed chelated complexes were more efficient than N -oxide-promoted runs with in situ generation of the chelated intermediates.…”
Section: Introduction Of Chirality During the Generation Of The Cyclo...mentioning
confidence: 99%
“…So far, the use of thioalkynes in [3+2] annulations has not been reported, although they have been successfully applied in [4+2], [3+2] and [2+2] cycloadditions as well as in the Pauson–Khand reaction . Only two examples of [3+2] annulations of thioalkynes were reported, but none of them was based on the use of DA cyclopropanes .…”
Section: Methodsmentioning
confidence: 99%
“…6). 43 These chiral auxiliaries act by transmitting their chirality to the metal cluster due to the chelation with a cobalt atom, which upon diastereoselective complexation of the olefin, controls the absolute configuration of the final cyclopentenone (Fig. 7).…”
Section: Using Chiral Auxiliariesmentioning
confidence: 99%
“…The chiral auxiliary is eliminated using samarium iodide, and a retro-Diels-Alder reaction can finally afford highly enantiomerically enriched 4-substituted cyclopentenones (Scheme 34). 43 Carretero has demonstrated the feasibility of carrying out the PKR with electron deficient olefins. Among the different electronic withdrawing groups used by this group, chiral sulfoxides attached Fig.…”
Section: Using Chiral Auxiliariesmentioning
confidence: 99%